Effect of plyometrics and pilates training on dynamic balance and core strength of karate players - Pal, S.; Yadav, J.; Sindhu, B.; Kalra, S. (Journal of Clinical & Diagnostic Research, 2021)
Introduction: The success of the karate player mainly depends on the balance and core strength. Improvement in these physical variables depends upon the type of exercise training used by the athletes. In the Indian context, there is lack of literature that supports the use of Pilates and Plyometric Training (PT) programme in training of Karate players. Therefore, to achieve success in the sport, best training method should be chosen by athletes or coaches. Aim: To compare and evaluate the effectiveness of two training programs Pilates and Plyometric on balance and core strength of National level male Karate athletes. Materials and Methods: The design of this study was experimental and sampling technique was simple random sampling. This study was conducted on a sample of 120 with 40 subjects in each group i.e., Experimental group A (Plyometric, N=40), Experimental group B (Pilates, N=40) and Control group C (N=40). The data was collected during 20th May 2018 to 10th February 2020. The national level male karate players in the age group of 18 to 24 years with playing experience of five years were included in the study. The plyometric and pilates training were carried out in experimental groups for three days per week for eight weeks and no training method was implemented in the control group. Three reading were recorded, at the baseline, at the end of 4th and 8th week. Dynamic balance and core strength were the outcome measurements which were measured by modified Star Excursion Balance Test (mSEBT) and isometric core strength tests respectively. All the data was analysed by SPSS version 2.0 and the descriptive stats noted as mean±SD. ANOVA post-hoc analysis were calculated with p-value significance set at <0.05. Results: After eight weeks of intervention, both experimental groups showed significant improvement in dynamic balance and core strength comparisons between the groups. When the pre-test and post-test values of the experimental groups have been compared at the 4th week and 8th week of the study showed significant improvement (p-value <0.001) in the mSEBT and Core strength of the plyometric group compared to pilates and control group. Conclusion: The findings of the present study revealed that plyometrics and pilates both can improve balance and core strength of karate players but the PT method had more positive and statistically better effects on core strength and dynamic balance than pilates group in the view of sports performance.